The dictionary of classical Hebrew - Clines, David J. A. (Sheffield, UK : Sheffield Academic Press, 1995)
"The Dictionary of Classical Hebrew": incorporates all Hebrew from the earliest times to c.200 CE; includes all the data from Ben Sira (Ecclesiasticus), the Dead Sea Scrolls and related texts, and the Hebrew inscriptions down to 200 CE; lists and analyses all occurrences of every Hebrew word (with the exception of a few very common words); gives an English translation of every Hebrew word and phrase cited in the dictionary; provides statistics for the number of occurrences of each word in each of the four corpora of Hebrew; concentrates on the common words rather than the rare ones; indexes all the nouns to their verbal "root" and all the verbs to their "derived" nouns; is systematically based on modern linguistic principles; contains a word-frequency index and a list of all the sources for the Hebrew language, including all the manuscripts from Qumran; provides a comprehensive bibliography to scholarly studies on individual Hebrew words and an English-Hebrew index.
v. 4. Yodh - Lamedh.
Includes bibliographical references and indexes.
Keywords: Bible. -- language, style; Hebrew language -- Dictionaries -- English